Walt Whitman's New York: From Manhattan to Montauk - Christman, Henry M. (Rowman & Littlefield Publishers, 1998)
This is probably the most notable of all regional books about New York and Long Island. It is the work of Walt Whitman, and its pages reveal the serious professional journalist, and not seldom the poet, writing brave things in prose. The editor comments in his introduction, "Whitman, though a native of the New York area, loved it and wrote of it with the zeal and zest usually found only in those from elsewhere who have made New York their chosen home." Indeed, he lived in the region for the first forty-two years of his life; successfuly edited newspapers in Brooklyn, Manhattan, and Long Island; and wrote for many years following. The articles collected in this volume by Henry M. Christman were conceived as a book by their author but appeared in a series entitled "Brooklyniana" that appeared in the Brooklyn Standard. All bear the impress of Whitman's humanity and show the breadth of his interest in "the great play of life and business going on around us."